Impact of Cash Transfers Programme on Agricultural Production in Kenya: Focus on the Orphans and Vulnerable Children - David Katuta Ndolo (European Scientific Journal, ESJ, 2023)
Orphans and children from low-income households are especially vulnerable to the adverse effects of a widening wealth gap, given their position at the bottom of the social hierarchy. The majority of these households reside in rural areas and are primarily involved in farming activities. Governments can employ initiatives such as cash transfers (CTs) to alleviate the impact of economic uncertainty on the impoverished. After the implementation of the cash transfer program targeting orphans and vulnerable children in Kenya, this paper focuses on analysing its impact on agricultural output and labor supply. Employing a difference-in-differences estimation method, the study revealed that families of orphans and vulnerable children who received cash transfers experienced an 8.5% increase in agricultural output. Expenditure on labor supply and recruitment of employees for agricultural activities within households headed by orphans and vulnerable children surged by 121% following the program's initiation, as compared to households led by non-orphans and non-vulnerable children. These findings offer further evidence supporting the necessity for governments to augment both direct and indirect cash transfers to marginalized populations, particularly orphans. This underscores the significant impact cash transfers wield on their overall quality of life. Implementing affirmative policies targeted at these groups remains crucial for bolstering their social well-being. Future studies should include youths who are ravaged by high rates of unemployment due to limited opportunities within various governments.